DISPENSER KAYU - Misbah Misbah; Jati Widagdo (SULUH: Jurnal Seni Desain Budaya, 2019)
Dispenser is furniture furniture that is often found in various places. Apart from its main function as a storage for drinking water, the dispenser that the author has made has been designed and made as an aesthetic object in a space. . As a place to store drinking water dispenser that the author made. This aims to provide other functions besides its main function. Based on this, the problems raised in this case are (1) How to make a dispenser design, which is able to support human activities, (2) How to make a dispenser by including Jepara ornaments as decorative elements, which can be an attraction, The use of Jepara ornaments aims, so that Indonesian furniture designers should still care about the arts and culture of the archipelago, namely by applying handicraft products into them, so that they can become a media of socialization and appreciation of Indonesian culture.